Analysis of Students' Creative Thinking Skills Viewed from Learning Styles in Problem-Based Learning Assisted by Nadhom Risalah Fi Ilmi Hisab - Muchammad Imron; Masrukan, Masrukan; Asih, Tri Sri Noor (Universitas Negeri Semarang, 2025)
This study aims to analyze students' creative thinking skills on integer material viewed from their learning styles in problem-based learning assisted by Nadhom Risalah Fi Ilmi Hisab. This study employs a qualitative research approach. The research subjects consisted of 6 students of class VII C of SMP Tahfidh Ma’had Yasin in the 2024/2025 academic year, namely 2 students with visual learning styles, 2 students with auditory learning styles, and 2 students with kinesthetic learning styles. Data collection techniques include tests, questionnaires, and interviews, with instruments such as a creative thinking skills test, a learning style questionnaire, and interview guidelines. The results of the study show that students with a visual learning style successfully meet the indicators of flexibility, originality, and elaboration well but are still lacking in fluency. Students with an auditory learning style successfully meet the indicators of fluency, flexibility, originality, and elaboration well. Meanwhile, students with a kinesthetic learning style successfully meet the indicators of fluency, originality, and elaboration well but still fall short on flexibility.